2014
DOI: 10.1186/2193-1801-3-125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic factors associated with diagnostic wait times by breast cancer detection method

Abstract: IntroductionAlthough prognostic differences between screen-detected, interval and symptomatic breast cancers are known, factors associated with wait times to diagnosis among these three groups have not been studied.MethodsOf the 16,373 invasive breast cancers diagnosed between January 1, 1995 and December 31, 2003 in a cohort of Ontario women aged 50 to 69, a random sample (N = 2,615) were selected for chart abstraction. Eligible women were classified according to detection method; screen-detected (n = 1181), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(43 reference statements)
2
12
1
1
Order By: Relevance
“…Our results are similar to that of several large USA and Canadian studies reporting median times between 12 and 16 days with approximately 80% of women diagnosed within 30 days [63,64,65,66]. BreastScreen Australia recommends women with a screen-detected abnormality should be assessed within 28 days, with their most recent evaluation report indicating around 20% of women were not fully assessed within that time frame [67], similar to our study results.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to that of several large USA and Canadian studies reporting median times between 12 and 16 days with approximately 80% of women diagnosed within 30 days [63,64,65,66]. BreastScreen Australia recommends women with a screen-detected abnormality should be assessed within 28 days, with their most recent evaluation report indicating around 20% of women were not fully assessed within that time frame [67], similar to our study results.…”
Section: Discussionsupporting
confidence: 90%
“…The method of result notification (with telephone and letter notification associated with longer delays than in‐person notification), as well as the use of navigators, rapid diagnostic units, and organized screening programs, influence the timeliness of follow‐up . Procedures that reduce the number of interfaces involved (such as use of core needle biopsy rather than open biopsy for abnormal mammograms) may reduce the time to biopsy …”
Section: Improving Diagnostic Testing After a Positive Screenmentioning
confidence: 99%
“…33,127,131 Procedures that reduce the number of interfaces involved (such as use of core needle biopsy rather than open biopsy for abnormal mammograms) may reduce the time to biopsy. 132 Thus, overcoming barriers to timely follow-up likely will require multilevel interventions to mitigate multiple barriers, 133 but evidence is limited regarding effective interventions. 2,3 A recent systematic review of interventions to improve follow-up of positive FIT found only limited evidence that supported the use of patient navigators or giving providers reminders or performance data.…”
Section: Improving Diagnostic Testing After a Positive Screenmentioning
confidence: 99%
“…Accordingly, we found longer WT, due to diagnostic WT, associated with not being taxable. On the contrary, a higher income quintile was also associated with longer treatment WT, but it was not a predictor of diagnostic WT, whatever the mode of detection . No difference in treatment WT or in overall WT by deprivation quintile was found in two studies in the UK, nor in the study reported by Gorey et al in Ontario …”
Section: Discussionmentioning
confidence: 71%
“…Because of missing data, only 653 women were analyzed in the multivariate models. The three median WTs of these 653 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] women (44 days (IQR 5 33-60) for overall WT, 9 days (IQR 5 3-20) for diagnostic WT and 31 days (IQR 5 23-42) for treatment WT) did not differ from those of the 973 women initially included in our descriptive analyses. The lack of social support was strongly related to WTs but was missing for 81 women.…”
Section: Sensitivity Analysesmentioning
confidence: 99%